Ensaio comparativo de cultivares de soja em época convencional em selvíria, ms: Características agronômicas e produtividade - da Silva, Josué Bispo; Lazarini, Edson [UNESP]; da Silva, Alexandre Marques [UNESP]; Reco, Paulo César (My University, 2010)
The performance evaluation it's an important procedure for recommendation of a cultivar to an specific region, because the better adapted will present superior development and bigger level of productivity. The work aimed evaluates the behavior of soybean cultivars IAC 15-1, IAC 18, IAC 20, BRS 133, FT-2000, KI-S 602 RCH, MT/BRS-55 (Uirapuru), MT/BR-45 (Paiaguás), MT/BRS-51 (Xingu), KI-S 801, MSOY 7701, MT/BR-49 (Pioneer), EMBRAPA 65 (Itapoty), EMBRAPA 64 (Ponta Porã), EMBRAPA 61, IAC 8-2, IAC 19, Crystalline FT RCH, KI-S 702, IAC Foscarin 31, IAC-PL1 and MT/BRS-46 (Conquista), related to agronomical characteristics of plants (cycle, height, height of first beans insertion and stand) and productivity of grains, when sowed in conventional time. The experimental design was randomized blocks with four replicates, and the averages compared with Tukey Test (5%). It is viable soybean production at Selvíria, MS, because practically all cultivars evaluated are adapted to the soil and climate conditions of that area. To cultivar KI-S 801, the use of smaller stand to the observed in that work it can avoid lodging. Caution should be had to use cultivar MT/BRS-55 (Uirapuru).
Comparative study among different cultivars at conventional time in Selvíria, Ms: Agronomical Characteristics And Productivity
Keywords: Genotype; Glycine max; Production; Regional study